Marked recent declines in boron in Baltic Sea cod otoliths – a bellwether of incipient acidification in a vast hypoxic system? - Limburg, Karin E.; Heimbrand, Yvette; Kuliński, Karol (Biogeosciences, 2023)
Ocean acidification is spreading globally as a result of anthropogenic CO2 emissions, but the Baltic Sea has until recently been thought to be relatively well-buffered by terrigenous inputs of alkalinity from its watershed. We discovered a 3- to 5-fold decline in boron (as B : Ca) in otoliths of eastern Baltic cod (EBC) between the late 1990s and 2021. Examining a time series of EBC otoliths, we found varying levels of B : Ca starting in the 1980s, with the most recent years showing an all-time low for this period. This trend correlates with declines in pH and dissolved oxygen but not with changes in salinity. We examined possible physiological influences on B : Ca by including a collection of Icelandic cod as an “out-group”. Icelandic cod otoliths showed strongly positive correlations of B : Ca with physiologically regulated P : Ca; this was not the case for EBC. Finally, B : Ca in EBC otoliths is negatively correlated, to some extent, with Mn : Mg, a proposed proxy for hypoxia exposure. This negative relationship is hypothesized to reflect the dual phenomena of hypoxia and acidification as a result of decomposition of large algal blooms. Taken together, the otolith biomarkers Mn : Mg and B : Ca in cod suggest a general increase in both hypoxia and acidification within the Baltic intermediate and deep waters in the last decade.